"I'm Not a Doctor. I'm a Nurse": Reparative Boundary-Work in Nurse Practitioner Education. (April 2019) - Trotter, LaTonya
Boundary-work is constitutive of both jurisdiction and professional identities. For groups attempting domain expansion, changed boundaries present risks for group cohesion. In this article, I examine the boundary-work that nurse-practitioners-in-training perform to negotiate the contradictions of moving into the new terrain of diagnostic medicine. I found that students engaged in reparative boundary-work that re-inscribed the new terrain of the nurse practitioner into the "old work" of bedside nursing. These strategies not only resolved the contradictions of nurse practitioner identity, but they also provided strategies of action for negotiating new relationships with future physician colleagues. This analysis demonstrates that the defense of breached boundaries is activated not only by external threats but also by the internal threats of jurisdictional expansion.